ISOLASI SENYAWA STEROID DARI AKAR TUMBUHAN ASAM KANDIS (Garcinia cowa Roxb. ex DC) SEBAGAI OBAT PENURUN DEMAM - Darwati; Nurlelasari; Tri Mayanti (Jurnal Penelitian Hasil Hutan, 2019)
Garcinia cowa is belong to the Guttiferae family. In Indonesia this plant is locally named asam kandis. Traditionally, the stem bark of Garcinia cowa are used as antipyretic dan antimicroba, the fruits and leaves used as expectorat, and laxative, and the roots is used for fever medicine. The variaty use are Garcinia cowa as traditional medicine is based it chemical compounds. In our continuing phytochemical investigation to found the secondary metabolite compounds of Garcinia plants found in Indonesia, The objective of this research was to find the steroid compound from the roots of Garcinia cowa. Isolation was conducted by extraction and chromatography methods. The structure of this compound was determined based on spectroscopic data from NMR and comparison with the reported data.